Prace i uchwały II Polskiego Synodu Plenarnego - Janczewski, Zbigniew (Prawo Kanoniczne, 2001)
The Second Plenary Polish Synod was from the year 1991 to the year 1999. The Synod had three phases: the first - preparatory, the second - the works on the parishes and on the dioceses and the thirst - editorial work of the final documents and voting on resolutions by the polish bishops. The resolutions of the Synod consists of fourteen parts. Every part has the fragment about theological description, sociological description and pastoral conclusions. In the Second Plenary Polish Synod was participating not only the clergy but also the lay persons.